Continuous cultivation of human hamstring tenocytes on microcarriers in a spinner flask bioreactor system. (18th October 2013) - Stich, Stefan; Ibold, Yvonne; Abbas, Amro; Ullah, Mujib; Sittinger, Michael; Ringe, Jochen; Schulze‐Tanzil, Gundula; Müller, Christiane; Kohl, Benjamin; John, Thilo
<x xml:space="preserve">Abstract</x> Tendon healing is a time consuming process leading to the formation of a functionally altered reparative tissue. Tissue engineering‐based tendon reconstruction is attracting more and more interest. The aim of this study was to establish tenocyte expansion on microcarriers in continuous bioreactor cultures and to study tenocyte behavior during this new approach. Human hamstring tendon‐derived tenocytes were expanded in monolayer culture before being seeded at two different seeding densities (2.00 and 4.00 × 106 cells/1000 cm2 surface) on Cytodex™ type 3 microcarriers. Tenocytes' vitality, growth kinetics and glucose/lactic acid metabolism were determined dependent on the seeding densities and stirring velocities (20 or 40 rpm) in a spinner flask bioreactor over a period of 2 weeks. Gene expression profiles of tendon extracellular matrix (ECM) markers (type I/III collagen, decorin, cartilage oligomeric protein [COMP], aggrecan) and the tendon marker scleraxis were analyzed using real time detection polymerase chain reaction (RTD‐PCR). Type I collagen and decorin deposition was demonstrated applying immunolabeling. Tenocytes adhered on the carriers, remained vital, proliferated and revealed an increasing glucose consumption and lactic acid formation under all culture conditions. "Bead‐to‐bead" transfer of cells from one microcarrier to another, a prerequisite for continuous tenocyte expansion, was demonstrated by scanning electron microscopy. Type I and type III collagen gene expression was mainly unaffected, whereas aggrecan and partly also decorin and COMP expression was significantly downregulated compared to monolayer cultures. Scleraxis gene expression revealed no significant regulation on the carriers. In conclusion, tenocytes could be successfully expanded on microcarriers. Therefore, bioreactors are promising tools for continuous tenocyte expansion. © 2013 American Institute of Chemical Engineers Biotechnol. Prog., 30:142–151, 2014